Vegetable Farming and its Impacts on Economic Status of the people Living in Kalika Municipality - Dhakal, Chandra Prasad (International Journal of Atharva, 2025)
This study investigates the socio-economic transformations driven by the shift from subsistence to commercial vegetable farming in Kalika Municipality, Ward No. 8, Nepal. Using a mixed-methods approach, data was collected from 20 vegetable farmers through surveys and interviews to analyze changes in their livelihoods.The findings reveal significant positive impacts. Economically, vegetable farming provided a reliable year-round income, leading to a substantial increase in annual earnings and savings for 90% of respondents. This enhanced financial stability enabled investments in children's education, healthcare, and improved festival celebrations. Socially, the transition altered time use, with leisure time being reallocated to productive farming activities. The study also noted improvements in dressing patterns and health sanitation for a majority of households.The research concludes that commercial vegetable farming acts as a powerful catalyst for socio-economic development in rural Nepal. It effectively reduces poverty, enhances food security, and improves overall quality of life by providing sustainable employment and empowering local communities. The study underscores the importance of continued support through agricultural policies, market access, and capacity-building programs to sustain and amplify these benefits.